2014
DOI: 10.1080/03670244.2013.834818
|View full text |Cite
|
Sign up to set email alerts
|

Length of Migration and Eating Habits of Portuguese University Students Living in London, United Kingdom

Abstract: Objective: To gauge the effect of different migration periods on the eating pattern of Portuguese university students.Methods/subjects: Fifty-five Portuguese students participated in a survey of food practices before and after moving from Portugal to London. The students were divided into two groups, the short term migration group, living in London less than one year, and the long term migration group, living in London more than one year. Forty-six English university students were used as a comparison to the P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 49 publications
(37 reference statements)
1
7
1
2
Order By: Relevance
“…Besides that, food incompatibilities are also stressors which disturb in student's adjustment. As what was found in other previous study (Vilela et al, 2014;Ye & Juni, 2018), living conditions attributed by climate, eating habits, housing condition, the way of transportation and other factors can influence acculturative stress among foreign students in host country.…”
Section: Discussionsupporting
confidence: 68%
“…Besides that, food incompatibilities are also stressors which disturb in student's adjustment. As what was found in other previous study (Vilela et al, 2014;Ye & Juni, 2018), living conditions attributed by climate, eating habits, housing condition, the way of transportation and other factors can influence acculturative stress among foreign students in host country.…”
Section: Discussionsupporting
confidence: 68%
“…Another point of concern is the higher median duration of residency in London of men compared to women, which could have contributed to the higher likelihood of men to change and of women to maintain their dietary habits. Another study in the same sample of Portuguese university students found that students living in London for a long term showed more dietary changes and seemed to be more acculturated than students living in London for a short term, but that study did not take sex into account . Although our results could be influenced by the different duration of residency in the new country, they seem to be due, at least in part, to sex‐related differences.…”
Section: Discussioncontrasting
confidence: 57%
“…Another study in the same sample of Portuguese university students found that students living in London for a long term showed more dietary changes and seemed to be more acculturated than students living in London for a short term, but that study did not take sex into account. 30 Although our results could be influenced by the different duration of residency in the new country, they seem to be due, at least in part, to sex-related differences. The lack of detailed information on participants' characteristics could compromise the understanding of our findings because we cannot rule out the influence of other variables not collected in the present study.…”
Section: (D)mentioning
confidence: 58%
“…Students' accommodation/changes in living arrangements that some students encounter also influence their food choices where dietary intakes might feature unfavourable practices, especially for those not living with parents or those who move to another county or country to attend university (10). For instance, Greek students faced difficulties in maintaining a traditional Mediterranean diet after leaving the family home and moving to Northern Europe (10), and the same was reported for Portuguese university students (11). Nonetheless, universities provide appropriate opportunities/environment to reach many young adults through nutrition education efforts to positively influence their dietary intakes and encourage them to embrace healthy food choices.…”
Section: Introductionmentioning
confidence: 95%